LEGAL ACTIONS VERZET AGAINTS EXECUTION CONFISCATION IN CIVIL CASE AT DISTRICT COURT SEMARANG (CASE STUDY COURT DECISION NO. 152/Pdt.Plw/2006/PN.SMG) - Ahmad Nurhuda, R. Benny Riyanto*), Marjo (Diponegoro Law Journal, 2013)
Plaintiff fears that the defendant would transfer the objects that result in execution cases can not be implemented because the object does not exist to make plaintiffs laying sequestration, but the problem is what if the object that is placed arresting turns of a third party.The purpose of this research is to find out how a third-party opposition procedure (Derden verzet) in the examination of civil cases in the District Court of Semarang and submission of the third party against Sita execution in Relation to Delay Execution.Method of approach used in this research, according to the type of research that studies the normative legal (juridical normative), it can be used more than one approach.Based on this research, that the data provided by the plaintiff must be able to be verified, but in this case the judge error in relying only on data provided by the plaintiff. The existence of a third party Resistance (Derden verzet) does not delay the execution, but it is possible to delay the execution during there are reason legally allowed to delay the execution. The decision which legally binding, the judge issued a Letter Withdrawal of Sita execution and ordered court clerks and the bailiff to immediately revoke the object of placing confiscated from verdict of execution confiscation.